Cross-Disciplinary Knowledge Connections and Bridging Journals: The Evolution of Business Scholarship from 1990 to 2010 - Yan, Jie; Belkhouja, Mustapha; Xiong, Jie (Management international / International Management / Gestiòn Internacional, 2021)
This article examines the evolution of business research through the cross-disciplinary dissemination of business knowledge. Drawing on social network analysis techniques, we explain how knowledge flows through citation networks cross-disciplinary boundaries; and we identify the role of core journals in that evolution. The empirical analysis is based on 4.58 million citations by 105,405 papers published in 252 journals between 1990 and 2010. Three important findings emerge from this analysis: (1) increased knowledge connections among disciplines, (2) changing influences of certain journals within and across disciplines, and (3) a few journals bridge multiple disciplines.